Skull Base Reconstruction following Surgical Treatment of Sinonasal Malignancies - Pool, Christopher; Abiri, Arash; Kuan, Edward C. (Journal of Neurological Surgery Reports, 2023)
Skull base defects following resection of anterior cranial fossa and sinonasal tumors are not uncommon. Advances in endoscopic techniques have allowed for entirely endonasal resection and reconstruction of these tumors. This article discusses techniques in the evaluation and management of anterior skull base defects.
Keywords: skull base reconstruction; anterior cranial base; sinonasal malignancy; nasoseptal flap